Food safety practices lacking in independent ethnic restaurants - Roberts, Kevin R.; Kwon, Junehee; Shanklin, Carol W.; Liu, Pei; Yen, Wen-Shen (My University, 2011)
This study compared compliance with the Food Code between ethnic and non-ethnic restaurants and identified specific food safety practices needing improvement. Frequencies for 275 individual Kansas Food Code violations and the number of critical and noncritical violations were compared between independent ethnic, chain ethnic, independent non-ethnic, and chain non-ethnic restaurants. Independent ethnic restaurants had significantly more critical and noncritical violations than the other three types of restaurants. The majority of differences in code violations were found between independent ethnic restaurants and the other three categories. Overall, non-ethnic restaurants had higher food code compliance scores than independent and chain ethnic restaurants.
Keywords: Ethnic; Compliance; Food safety; Food code; Practices; Restaurants